Study on the quenching depth and surface hardness of metal materials by laser quenching variable parameters - Ren, Dongdong; Zhang, Pengjun; Yu, Jiahui; Yao, Yangwu; Li, Xiaoyang (Frontiers in Physics, 2023)
Laser quenching is one of the most outstanding gear tooth surface quenching methods due to its high efficiency, environmental friendliness, and performance consistency. Since gear tooth surface laser quenching requires repeated scanning, changing the laser scanning velocity and power by program control can meet the needs of variable depth quenching. The effects of laser scanning velocity and output power on the quenching depth and surface Rockwell hardness after quenching were studied and experimentally analyzed. The result shows that by adjusting the parameters, the surface hardness of the specimen changes slightly with the actual received laser energy. However, the quenching depth can be consistent with the laser scanning velocity. The maximum surface Rockwell hardness that a laser quenched material can achieve depends on the material itself, not on the laser power or scanning velocity. Compared with accelerated laser quenching, decelerated laser quenching is more suitable for tooth surface machining due to the cumulative effect of energy within the quenching depth range of metal materials.